A governança hídrica multinível e a elaboração de cenários prospectivos na bacia hidrográfica transfronteiriça do Rio Quaraí/Cuareím, na fronteira do Brasil e do Uruguai. - Bervig, Aline Andressa (2022)
The demand for the use of water resources is increasingly intense to meet the basic and vital needs of humanity, as well as for its economic exploitation. Due to the situations in which they find themselves in shared basins, either in cooperation or in conflict by two or more countries, they become transboundary. In case of conflicts in these basins, there is a need to investigate them seeking their mitigation, and even taking decisions in the search for a definitive solution. To seek this understanding in transboundary watersheds, one of the possibilities is to put into practice multilevel governance, or, in the case of water resources, multilevel water governance. Both are known as a system of continuous negotiation between governments linked at different territorial levels, in addition to being inserted within political networks that go beyond the limits of the public sphere. Aiming at both long-term cooperation and short-term conflict resolution, it is possible to use prospecting, where this tool proposes to create possible scenarios for the future. And for water resources, both multilevel water governance and prospective scenarios are essential in the pursuit of rational and equitable use of this natural resource. In this sense, the study area was the transboundary watershed of the Quaraí/Cuareím River, located on the border between Brazil and Uruguay. The main objective is to develop prospective scenarios for the transboundary watershed of the Quaraí/Cuareím River, on the border between Brazil and Uruguay. To obtain the data, the following methods were used: the bibliographic review referring to the various topics that involved (border, management, multilevel governance, multilevel water governance, state rescheduling, the hydrographic basin and among others), the exchange of information with people and who are involved with the management and governance of the watershed and the elaboration of prospective scenarios through the method of the Frenchman Michel Godet. As a result, it is expected to demonstrate the causes and conflicts that occur in the transboundary watershed of the Quaraí/Cuareím River, as well as the multilevel water governance being applied in this spatial cut and, finally, generate proposals for the improvement of the use of natural resources.